Identification of antibiotics triggering the dissemination of antibiotic resistance genes by SXT/R391 elements using a dedicated high-throughput whole-cell biosensor assay. (21st October 2021) - Guilloteau, Hélène; Pradalier, Cédric; Roman, Véronica L; Bellanger, Xavier; Billard, Patrick; Merlin, Christophe
Abstract: Background: Mobile genetic elements (MGEs) are widely involved in the dissemination of antibiotic resistance genes and some of them, such as the integrative and conjugative element SXT, are even induced by specific antibiotics at sub-lethal concentrations. Objectives: This work explores collateral effects of a broad range of antibiotics on the mobility of the SXT MO10 element using a specifically designed high-throughput screening test. Methods: Twenty-five promoters involved in the mobility of SXT and six artificial constitutive promoters were transcriptionally fused to luxCDABE bioluminescent genes and introduced into Escherichia coli strains with or without SXT to build whole-cell biosensors for a large-scale screening involving 48 antibiotics. A bioluminescent assay implementing a classical agar diffusion approach was coupled to an automated data processing pipeline developed to extract and analyse luminescence data from over 2000 antibiotic/biosensor combination profiles. Results: In addition to quinolones previously reported as inducing the expression of SXT mobility genes, we found that specific antibiotics belonging to other classes, such as imipenem and azithromycin, also behave as inducers. The use of a control set of constitutive biosensors also revealed an unexpected intricate relationship between cell respiration and light production that allowed the identification of antibiotics interfering with the respiration process. Conclusions: The effect of antibiotics goes beyond the interaction with their primary cell targets and may lead to adverse effects such as triggering the dissemination of resistance by MGEs, sometimes in unpredictable ways. Identifying such MGE-triggering antibiotics is of prime importance for better controlling collateral effects during therapy.